Prescribing patterns and safety of biologics in immune-mediated rheumatic diseases: Karnataka biologics cohort study group experience - Vineeta Shobha; Vijay Rao; Anu Mohan Desai; Ramesh Jois; Chandrashekara Srikantiah; B G Dharmanand; Sharath Kumar; Pradeep Kumar; Chethana Dharmapalaiah; K M Mahendranath; Shiva Prasad; Manisha Daware; et al. (Indian Journal of Rheumatology)
Introduction: Biologics are widely used in Autoimmune rheumatologic diseases (AIRDs), however the need to capture real life data which monitors indications, adverse reactions cannot be over emphasized. Methods: This is a cross-sectional ambidirectional multi-center study conducted over 8 months from January 2016 to August 2016, across 12 tertiary care rheumatology centers in Karnataka, India conducted by members of the Karnataka Rheumatology Association. Results: The most common biologic prescribed is tumour necrosis factor antagonist etanercept. Commonest indication for biologics being Spondyloarthropathy group of disorders. The most common cause for stopping biologics is clinical improvement. Only 4.8% of patents discontinued biologics due to ADRs. Conclusion: The prescribing patterns, mode of use, prebiologics screening methods, and adverse event profile are similar across centres. Pre-screening for latent tuberculosis (TB) is consistent across centres, and TB prophylaxis appears to be effective in preventing its reactivation.